Heartbreak on the Serengeti - Robert Poole (Symphony in the Flint Hills, 2015)
To the Maasai it’s the place where the land runs on forever, but beyond the protected core of this iconic landscape, the land is running out.
Keywords: Serengeti; grassland; cape buffalo; animals; Maasai; native; people; tribe; East Africa; Crater Highland; Tanzinia; gazelles; Lake Magadi; cattle; cows; herders; farmers; ecosystem; zebras; elephants; hunting; poaching; Serengeti National Park; Grumeti Reserves; slave; wildebeest